Activation of Toll-like receptor 9 attenuates unilateral ureteral obstruction-induced renal fibrosis - Xin Bing-mu; Wang Xiao-xing; Jin Wen; Yan Hui-min; Cui Bing; Zhang Xiao-wei; Hua Fang; Yang Hong-zhen; Hu Zhuo-wei (Acta Pharmacologica Sinica, 2016)
Aim: To study whether activation of TLR9 by CpG-ODN would protect against and/or reverse renal fibrosis. Methods: Animals were treated with CpG-ODN before or after undergoing a unilateral ureteral obstruction (UUO) procedure. The interstitial fibrotic lesions of obstructed kidneys were evaluated using histology and immunohistostaining. The Th2-type cytokine profile and the expression and activity of sma and mad related protein (Smad)3, signal transducers and activators of transcription (Stat)3, extracellular regulated protein kinases (ERK), and p38 kinase were determined using RT-PCR or Western blot. Results: The obstructed kidneys displayed a significant increase in interstitial fibrosis, an infiltration of macrophages in the interstitium, and an enhanced expression of Th2 cytokines. Prophylactic application of CpG-ODN (40 μg/kg every 3 days from 2 h before UUO until the 14th day after UUO) suppressed the expression of α-smooth muscle actin, collagen deposition, and hydroxyproline in the UUO kidneys of rats. Moreover, CpG-ODN not only decreased the infiltration of macrophages but also inhibited the expression of chemokines CCL2 and CCL5, the Th2 cytokine IL-13, and the profibrogenic cytokines transforming growth factor (TGF)-β1 and plasminogen activator inhibitor (PAI)-1 in UUO kidneys of rats. Importantly, therapeutic administration of CpG-ODN (10 μg/mouse, ip, every 3 days from the 4th day to 21st day after UUO) reversed the established renal fibrosis, which was accompanied by significant reductions in the activity of ERK, Smad3, and Stat3 and an increase in the activity of p38 kinase. Conclusion: The activation of TLR9 by CpG-ODN attenuates UUO-induced renal fibrosis by reversing an immunosuppressive microenvironment in the fibrotic renal tissue, which might be a novel therapeutic strategy against fibrotic renal diseases.